Enzymatic Synthesis of 7′, 5′‐Bicyclo‐DNA Oligonucleotides. Issue 12 (24th April 2017) - Diafa, Stella; Evéquoz, Damien; Leumann, Christian J.; Hollenstein, Marcel
Abstract: The selection of artificial genetic polymers with tailor‐made properties for their application in synthetic biology requires the exploration of new nucleosidic scaffolds that can be used in selection experiments. Herein, we describe the synthesis of a bicyclo‐DNA triphosphate (i.e., 7′, 5′‐bc‐TTP) and show its potential to serve for the generation of new xenonucleic acids (XNAs) based on this scaffold. 7′, 5′‐bc‐TTP is a good substrate for Therminator DNA polymerase, and up to seven modified units can be incorporated into a growing DNA chain. In addition, this scaffold sustains XNA‐dependent DNA synthesis and potentially also XNA‐dependent XNA synthesis. However, DNA‐dependent XNA synthesis on longer templates is hampered by competitive misincorporation of deoxyadenosine triphosphate (dATP) caused by the slow rate of incorporation of 7′, 5′‐bc‐TTP. Abstract : In sequence : A bicyclo‐DNA triphosphate (i.e., 7′, 5′‐bc‐TTP) is positively identified as a potential xenonucleic acid (XNA) candidate: this triphosphate can be used for DNA‐dependent XNA synthesis and for XNA‐dependent XNA and DNA syntheses of short sequences if the Therminator DNA polymerase is used.